Anisakid nematodes (Nematoda: Anisakidae) from the marine fishes Plectropomus laevis Lacépède (Serranidae) and Sphyraena qenie Klunzinger (Sphyraenidae) off New Caledonia, including two new species of Hysterothylacium Ward & Magath, 1917 - Moravec, František; Justine, Jean-Lou (Systematic parasitology, 2015)
Based on light and scanning electron microscopical studies, two new species of Hysterothylacium Ward & Magath, 1917 (Nematoda: Anisakidae) are described from the digestive tract of perciform fishes off New Caledonia: H. alatum n. sp. from Plectropomus laevis (Lacépède) (Serranidae) and H. sphyraenae n. sp. from Sphyraena qenie Klunzinger (Sphyraenidae). The former species (H. alatum) is mainly characterised by its large body (male 42.05 mm, gravid females 51.18-87.38 mm long), the shape of the dorsal lip, conspicuously broad cervical alae, a short caecum and a long ventricular appendix, the length of the spicules (925 µm), the number (25 pairs) and distribution of the genital papillae and the tail tip bearing numerous minute cuticular protuberances. The other species (H. sphyraenae) is mainly characterised by the presence of narrow lateral alae, a short caecum and a long ventricular appendix, the length (762-830 µm) and shape of the spicules, the number (37-38 pairs) and arrangement of the genital papillae, and by the tail tip which lacks any distinct cuticular projections visible under the light microscope. In addition, and unidentifiable at the species level, conspicuously large (45.71-66.10 mm long) larvae of Contracaecum Railliet & Henry, 1912, were found in the body cavity of P. laevis, which serves as a paratenic host for this parasite.
Keywords: Fishes; Bass; New Caledonia; larva; Host-Parasite Interactions; Ascaridoidea; ryby; Female; Microscopy, Electron, Scanning; interakce hostitele a parazita; Gastrointestinal Tract; Percoidea; Species Specificity; druhová specificita; gastrointestinální trakt; mužské pohlaví; zvířata; Nová Kaledonie; ženské pohlaví; Animals; Larva; Male; mikroskopie elektronová rastrovací